Semantic and right temporal variant of FTD: Next generation sequencing genetic analysis on a single-center cohort - Rossi, Giacomina; Salvi, Erika; Mehmeti, Elkadia; Ricci, Martina; Villa, Cristina; Prioni, Sara; Moda, Fabio; Di Fede, Giuseppe; Tiraboschi, Pietro; Redaelli, Veronica; Coppola, Cinzia; Koch, Giacomo; et al. (Frontiers in Aging Neuroscience, 2022)
Semantic and right temporal variant of frontotemporal dementia (svFTD and rtvFTD) are rare clinical phenotypes in which, in most cases, the underlying pathology is TDP-43 proteinopathy. They are usually sporadic disorders, but recent evidences suggest a higher frequency of genetic mutations for the right temporal versus the semantic variant. However, the genetic basis of these forms is not clear. In this study we perform a genetic screening of a single-center cohort of svFTD and rtvFTD patients, aiming at identify the associated genetic variants. A panel of 73 dementia candidate genes has been analyzed by NGS target sequencing including both causal and risk/modifier genes in 23 patients (15 svFTD and 8 rtvFTD) and 73 healthy age-matched controls. We first performed a single variant analysis considering rare variants and then a gene-based aggregation analysis to evaluate the cumulative effects of multiple rare variants in a single gene. We found 12 variants in nearly 40% of patients (9/23), described as pathogenic or classified as VUS/likely pathogenic. The overall rate was higher in svFTD than in rtvFTD. Three mutations were located in MAPT gene and single mutations in the following genes: SQSTM1, VCP, PSEN1, TBK1, OPTN, CHCHD10, PRKN, DCTN1. Our study revealed the presence of variants in genes involved in pathological pathways, especially autophagy and inflammation. We suggest that molecular analysis should be performed in all svFTD and rtvFTD patients, to better understand the genotype-phenotype correlation and the pathogenetic mechanisms that could drive the clinical phenotypes in FTD.